1983
DOI: 10.1093/ajcn/38.6.936
|View full text |Cite
|
Sign up to set email alerts
|

Tea and coffee as sources of some minerals in the New Zealand diet

Abstract: Daily intakes of tea and coffee of a representative sample of adult New Zealanders (865 men and 1100 women) were calculated from 24-h dietary recalls. The mineral concentrations in tea and coffee samples were determined by atomic absorption spectrometry and used to estimate daily mineral intakes from these beverages. More than 80% consumed tea and about 60% consumed coffee on the day of the recall. The men drank significantly more tea than the women (p less than 0.001), but coffee intakes were similar. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 11 publications
2
17
0
2
Order By: Relevance
“…Drinking tea contributes to dietary mineral intake [12,21,26]. Depending on the quantity of tea daily consumed and the hardness of tea the mineral contents show alterations in individuals [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking tea contributes to dietary mineral intake [12,21,26]. Depending on the quantity of tea daily consumed and the hardness of tea the mineral contents show alterations in individuals [2].…”
Section: Resultsmentioning
confidence: 99%
“…Tea is known as a good source for K and Mn, in addition to the flavonoids in its composition or other beneficial components [7,20,26].…”
Section: Resultsmentioning
confidence: 99%
“…For moderate to heavy tea drinkers, defined in this study as those consuming at least 1 l (four mugs) black tea infusion per day, the values were significantly higher and dependent upon the concentration used for the Mn content of tea infusions. Previously, figures around 0.5 mg/100 g have been reported for the Mn content of black tea infusions although those as low as 0.1 mg/100 g have also been suggested (Gillies and Birkbeck, 1983;Matsushima et al, 1993). Clearly the type of tea, including its geographical origin, degree of fermentation prior to drying and leaf size, as well as type and temperature of water, length of brewing time and strength of tea brew will all impact upon the concentration of Mn and other nutrients present in the infusion.…”
Section: Discussionmentioning
confidence: 95%
“…Tea drinking is a potentially major source of dietary manganese (Mn) as 1 l (four standard mugs) of black tea is estimated to contain 1.8-5.2 mg Mn (Gillies and Birkbeck, 1983;Fraile and Flynn, 1991;Matsushima et al, 1993;Powell et al, 1998;Matsuura et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The determination of macronutrients, micronutrients and toxic elements in soluble coffee is of great general interest, particularly because of the importance of coffee in nutrition to millions of people around the world (Krivan et al, 1982). Previous work on the composition of coffee and its products is mainly concerned with the mineral contents and studies on toxic elements are scarcely reported (Clarke et al, 1974;Gillies et al, 1983;Horwitz et al, 1974;Kuennen et al, 1982;Kapur et al, 1974;Koch et al, 1989;Lara et al, 1975/76). No information exists on the content of arsenic and selenium in this product although a number of publications (Goulden et al, 1981;Nakahara et al, 1985;Nakahara, 1981;Nygaard et al, 1982;Oliveira et al, 1983;Pahlavanpour et al, 1980;Ybanez et al, 1992) demonstrated that hydride generation, followed by introduction of gaseous hydrides into an ICP was a suitable method for the determination of several trace elements, including arsenic and selenium, for which detection limits were inadequate for foods and related matrices when conventional pneumatic nebulization was used.…”
Section: Introductionmentioning
confidence: 99%